Association of drinking water and environmental sanitation with diarrhea among under-five children: Evidence from Kersa demographic and health surveillance site, eastern Ethiopia - Mulatu, Gutema; Ayana, Galana Mamo; Girma, Haileyesus; Mulugeta, Yohannis; Daraje, Gamachis; Geremew, Abraham; Dheresa, Merga (Frontiers in Public Health, 2022)
Abstract Background Despite globally the progression of eradicating burden of diarrhea-related morbidity and mortality in the past two decades diarrhea remains one of the common top causes of mortality and morbidity. The Sub-Saharan African (SSA) countries where there is inadequate safe water supply and sanitation. However there is the dearth of literature estimate the impact of drinking water and sanitation service in childhood diarrhea in Kersa Demographic and Health Surveillance. Therefore, the current study aimed to assess the prevalence and effect of water supply and environmental sanitation on diarrhea among under-five children’s from 2017-2021 in Kersa Demographic and Health Surveillance, Eastern Ethiopia. Method: A prospective cohort study design was implemented among 6,261 under five children’s from Kersa Health Demographic Surveillance System (HDSS), Eastern Ethiopia from January 1, 2016 through December 31, 2021. Data were extracted from the datasets using STATA statistical software. The binary logistic regression was used to identify impact water supply and environmental sanitation on diarrhea by controlling important confounders. The adjusted odds ratio (AOR) with 95% confidence interval measure the association. Result: The current study showed that Among 6,261 under five children’s 2,614 of them had develop active diarrhea during the follow-up time. The final model depicted that having media exposure 22% [AOR ═ 0.78 CI: (0.61, 0.98)], protected tube well source of drinking water 50% [AOR═ 1.51, CI: (1.33, 171)], unprotected tube well source of drinking water66% [AOR ═ 1.66 CI: (1.27, 2.18), having toilet facility 13% [AOR ═ 0.87 CI: (0.78, 0.97), and accessibility of source of water [AOR ═ 1.17 CI: (1.05, 1.30) show significant association of with diarrhea among under five children’s Conclusion: The prevalence of diarrhea is found to be high in Kersa District. Lack of latrine, unimproved drinking water source, distance from drinking water was the main predicting factor of under-five diarrhea. Thus, increasing the adequacy of safe drinking water and sanitation should be given priority in the study setting.